Skin-Limited IgA Vasculitis: A Unique Presentation in an Adult Without Renal Involvement - Christian Cook; Jiwoo Kim; Escher Howard-Williams; Evan Raff (Annals of Internal Medicine: Clinical Cases)
We describe a rare case of skin-limited immunoglobulin A vasculitis (IgAV) in an adult with polycythemia vera (PV), a myeloproliferative neoplasm more commonly associated with IgA nephropathy (IgAN) than IgAV. Diagnosis was confirmed by biopsy showing IgA-dominant leukocytoclastic vasculitis without systemic involvement. Our patient was treated supportively for IgAV and with ruxolitinib for PV, with resolution of skin findings and no systemic progression. Although vasculitis is more commonly associated with myelodysplastic syndromes, its occurrence with PV is rare. Careful evaluation for renal involvement in IgAV is essential to guide management and to monitor for systemic progression, particularly renal manifestations.